X-Ray Fluorescence Determination of Trace Gold in an Ion-Exchange Resin - Mikhailov, I. F.; Baturin, A. A.; Mikhailov, A. I.; Fomina, L. P. (Pleiades Publishing, Ltd., 2014)
The use of portable X ray optics with a secondary radiator in the determination of trace gold in an ion exchange resin within the mass fraction range of 1–50 ppm is described. It is shown that the secondary radiator design with primary radiation filtering allows one to determine trace gold in an ion exchange resin when the mass fraction of gold is lower than 1 ppm.
Keywords: X-ray fluorescence analysis; secondary radiator; trace impurities; calibration characteristic; detec tion limit